Studi Kasus Penerapan Latihan Batuk Efektif Terhadap Perubahan Pola Napas Pasien Tuberkulosis Paru : Case Study Of The Application Of Effective Cough Exercises Against Airway Clearance Of Pulmonary Tuberculosis Patients - Dewi Sartiya Rini; Hasrina Hasrina (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Complaints of shortness of breath are one of the symptoms that arise in patients with Pulmonary Tuberculosis. This condition certainly requires proper nursing handling, namely through airway management nursing actions. The purpose of this study was to identify the application of airway management to changes in breathing patterns in Mr.S with pulmonary tuberculosis. The method used in research is a descriptive method with a case study approach. The respondent in this case study research was Mr.S with a medical diagnosis of pulmonary tuberculosis who was undergoing treatment in the Az-Zahra treatment room of RSU Dewi Sartika Kendari City. This case study was conducted from February 15, 2022 to February 22, 2022. The focus of the study is clients who experience impaired oxygenation needs characterized by shortness of breath and breathing frequency above 20x / minute, the instrument used is the format of assessment to nursing evaluation. The method of data collection starts from interviews and physical examinations. The results of the study found that Mr. S had difficulty removing his phlegm and the frequency of breathing was 28x / minute, the nursing diagnosis at Mr. S was that airway clearance was not effective related to secretions in the airway. The nursing intervention carried out is airway management which is carried out for 4 days according to the planned intervention. At the end of the evaluation, airway clearance was not effective in patients with resolved pulmonary tuberculosis, marked by a change in breathing frequency to 20x / minute. It is hoped that health workers can apply nursing care to pulmonary tuberculosis clients who experience oxygenation problems more optimally in order to improve the quality of hospital services